The use of flow rack as an effort to implement kaizen in an effort to increase the production of stepwagon car seats at PT YSC Japan - Elgrid Tornado Ridwan; Kurniawan Sigit Wahyudi; Zainal Arifin (Journal of Automotive and Mechanical Applied Technology, 2024)
This study aims to: (1) analyze the performance data of workers at PT. YSC Japan before the implementation of an innovation involving the addition of a Flow Rack; (2) examine the process of adding the Flow Rack and its impact on worker performance at PT. YSC Japan; and (3) evaluate how the Flow Rack innovation enhances worker productivity at PT. YSC Japan. The study employs the Kaizen concept using the 8-Step Improvement method, with a fishbone diagram utilized for cause-and-effect analysis. Data were collected through observation and documentation, using instruments such as a logbook, observation sheet, and smartphone. Descriptive quantitative analysis was conducted to compare production speeds before and after process improvements. The findings reveal that: (1) PT. YSC Japan required efficiency enhancements, as production on the Line Front Cushion Stepwagon experienced a loss time of 90 seconds per 22 pieces, resulting in a production time of 38.7 seconds per piece; (2) the application of the Kaizen concept, using the 8-Step Improvement method, successfully improved productivity through the addition of a Flow Rack as a storage innovation; and (3) after implementing this change, PT. YSC Japan achieved a 10.3% efficiency improvement, reducing production time to 34.7 seconds per piece.